Organizational Structure or Lecturer Behavior: Which One Provides the Greatest Mediation on the Influence of Professional Competence on Lecturer Performance? - Hidayat, Ahmad; Wahyudin, Dian; Halim, Paisal; Badruddin, Syamsiah; Daud, Akhmad Syarifuddin (CENTRAL ASIA AND THE CAUCASUS, 2022)
The research aims to analyze the impact of qualified faculty with organizational structure and lecturer behaviour as mediating variables. Researchers apply a quantitative research method with a survey technique to address the test hypotheses. The cluster random sampling technique is used for 170 respondents. The instrument of an organizational structure, professional competence, lecturer attitude, and lecturer performance is validated with loading factor value and VFE, while the Cronbach-Alpha measures reliability. The results of path analysis show that professional competence has a favourable influence on lecturer behaviour and organizational structure but does not have any on lecturer performance. In addition, organizational structure and lecturer behaviour positively influence lecturer performance, where Organizational structure intervenes significantly between professional skill and lecturer accomplishment.